Analisis Kasus Judi Online di Asia Tenggara - Saepul, Muhammad Rayhan; Rifa’I, Maulana Pradibta Eka (Peneliti.net, 2025)
Online gambling has become a disturbing phenomenon in Southeast Asia. Along with the increasingly sophisticated development of technology, this activity is expanding and its modus operandi is becoming more diverse. Online gambling operators take advantage of technology to operate gambling sites more effectively, reach more users, and hide their tracks from law enforcement. This makes online gambling a serious challenge for countries in this region. Using advanced technology, online gambling operators are able to quickly switch sites whenever there is an attempt to shut down by the authorities. They also often change bank accounts to hide the flow of funds, using encryption methods and complex money laundering techniques to disguise their transactions. In fact, some operators combine the proceeds from online gambling with income from legitimate businesses, making it difficult to distinguish between illegal and legal funds. This diverse modus operandi shows how sophisticated the methods used by the operators to avoid detection. To address this issue, close cooperation is needed among countries in Southeast Asia. Effective law enforcement must include comprehensive and adaptive strategies, including the use of advanced technology to track and analyze suspicious financial transactions. In addition, increasing public awareness of the risks and negative impacts of online gambling is crucial. Intensive public education can help reduce the number of victims and increase public vigilance against the modus operandi of the operators. With a comprehensive approach and good coordination, it is hoped that efforts to combat online gambling can be more effective in this region. Keywords: Online gambling, Southeast Asia, technology